Optical Delay Interferometers and their Application for Self-coherent Detection - Li, Jingshi (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2013)
Self-coherent receivers are promising candidates for reception of 100 Gbit/s data rates in optical networks. Self-coherent receivers consist of multiple optical delay interferometers (DI) with high-speed photodiodes attached to the outputs. By DSP of the photo currents it becomes possible to receive coherently modulated optical signals. Especially promising for 100 Gbit/s networks is the PolMUX DQPSK format, the self-coherent reception of which is described in detail.